Mapping the conceptual structure of entrepreneurship knowledge in Iran: A co-word Analysis - Hamid Ahmadi; Mahdi Husseinpour (پژوهشنامه علم سنجی)
Purpose: Entrepreneurship involves the initiation and management of a new business, which can result in value creation, job opportunities, and innovation. Entrepreneurship research includes the scientific and promotional activities undertaken by researchers in this field to explain, investigate, and analyze various entrepreneurial and economic factors and dimensions related to management and other business issues. The field of entrepreneurship in Iran has garnered significant interest from both organizational and individual researchers. This growth has necessitated an examination of the research framework from a conceptual perspective, employing scientometric techniques. Therefore, this research examines the activities in this field through a review of articles to establish a framework for evaluating the concepts and comparing them with international efforts. In this research, we seek to answer two fundamental questions: What is currently happening in the field of entrepreneurship research in Iran? And what conceptual dimensions have researchers focused on?Methodology: This research is applied in nature and has been conducted using scientometric techniques, including co-word analysis, information clustering, and conceptual network analysis. The research tools utilized include scientometric software such as Ravar_matrix, Ucinet, NetDraw, and VOSviewer. The research community encompasses all articles in the field of entrepreneurship published in domestic journals from 1994 to October 2023.Findings: The findings indicate that over the past two decades, research in the field of entrepreneurship in Iran has grown significantly, with many researchers contributing to its scientific productions. The results of the co-word analysis indicated that over 3,000 concepts were identified in research within this field in Iran. Among these, the concepts of "organizational entrepreneurship, entrepreneurship education, and innovation" were the most frequently mentioned. Additionally, the co-word pairs "entrepreneurship-organization", "entrepreneurship-development" and "entrepreneurship-village" had the highest number of co-occurrences. In addition, the concepts of social entrepreneurship, entrepreneurship, and academic entrepreneurship have been identified as emerging themes in research. The clustering results indicate that the body of knowledge in this field in Iran comprises seven main clusters.The first cluster, which pertains to organizational entrepreneurship, the second cluster focuses on the expansion and development of entrepreneurship, and the third cluster related to academic and knowledge-based entrepreneurship are ranked first to third, respectively, in terms of the number of concepts. Other clusters include the fourth cluster, which focuses on the empowerment of entrepreneurship in the community (social entrepreneurship) with 11 concepts; the fifth cluster, which examines the role of creativity, innovation, and risk-taking in entrepreneurship and business, comprising 10 concepts; the sixth cluster, which addresses the role of information and communication technology and knowledge-based companies, also with 10 concepts; and the seventh cluster, which explores culture, individual, and environmental factors in the field of entrepreneurship (individual entrepreneurship) with 7 concepts. Conceptual network analysis reveals that the concepts within this field exhibit numerous interrelationships, with an average network density of 0.2671. This indicates that the network is relatively dense. This statistic indicates that approximately 26% of the connections within the network are established, suggesting that the conceptual network of entrepreneurship in Iran is quite dense. Furthermore, the concepts of "organizational entrepreneurship, innovation, rural entrepreneurship, entrepreneurship development, and entrepreneurship education" exhibit a robust and high-density network.Conclusion: Solving societal problems relies on the development of new energy solutions through an entrepreneurial approach. Consequently, the academic sector of the country, as the primary foundation for the production and dissemination of entrepreneurial knowledge, plays a crucial role in advancing research activities in this knowledge-driven field. Undoubtedly, addressing the ever-increasing challenges faced by societies, university education, and the influence of information technology has significantly contributed to the growth of research in the field of entrepreneurship in Iran. The findings of this research offer a comprehensive overview of the issues discussed within this field of study. Specifically, according to articles in this field, the knowledge clusters of entrepreneurship in Iran are comparable to those at the global level. Additionally, Iranian researchers have focused on areas conducive to entrepreneurship in their studies.Also, based on the network's density number, it can be concluded that the concepts exhibit an acceptable relationship with one another, indicating a degree of conceptual convergence in entrepreneurship research. This study was conducted in response to the research proposal by Khaseh et al. (2017). It is hoped that the officials, curators, and researchers involved in the advancement of this field will utilize the findings of this research.